Resin-reinforced glass ionomer cement composition for dental luting with excellent adhesion and removability of excess cement
By adding subunit ketone compounds to dental combined resin-reinforced glass ionic cement and adjusting the ratio of polyvinyl acids and water, the problem of insufficient maintenance time and prone to tearing in the semi-hardened state of excess resin in the prior art is solved, and a safer and more efficient removal process is achieved.
Patent Information
- Application Number
- JP2023168927
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-28
- Publication Date
- 2025-04-09
AI Technical Summary
When removing excess resin, the existing dental combined resin-reinforced glass ionic cement has insufficient maintenance time in the semi-hardened state and is difficult to remove, and the excess resin is prone to tear, affecting the removal efficiency and safety.
Using a resin-reinforced glass ionic cement composition containing subunit ketone compounds, the maintenance time of the semi-hardened state is extended and the tear resistance of the excess resin is improved by adjusting the content of polyvinyl acids in the second dose and the ratio of water.
It achieves the extension of the semi-sclerosis state of excess resin in dental applications, facilitates removal, and improves the safety and efficiency of the removal process, reducing the risk of periodontal disease.
Smart Images

Figure 2025058783000001 
Figure 2025058783000002 
Figure 2025058783000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin-reinforced glass ionomer cement composition for dental bonding that is useful as a dental cement for bonding and / or affixing dental prosthetic devices to teeth. [Background technology]
[0002] In clinical dentistry, dental cements are used as materials for adhering and / or bonding dental prosthetic devices such as crowns, inlays, and bridges to teeth whose shapes have been partially damaged by caries, fractures, etc. Currently, the main dental cements in use include adhesive resin cements, glass ionomer cements for bonding, and resin-reinforced glass ionomer cements for bonding. The most important basic property required for these dental cements is that they are adhesive to tooth structure. In addition, the coating thickness (thickness of the cement layer between the tooth and the dental prosthetic device) is also required to be thin so that the lifting of the dental prosthetic device is minimized when applied to the tooth.
[0003] Among them, resin-reinforced glass ionomer cement for luting contains the main components of adhesive resin cement and glass ionomer cement for luting, and is a useful material that combines the high mechanical properties of the former with the properties of the latter, such as strengthening tooth structure by sustained release of fluoride. For example, Patent Document 1 discloses that a powder-liquid type dental resin-reinforced glass ionomer cement, which is made of a powder material containing fluoroaluminosilicate glass particles and polyalkenoic acid powder in a specific ratio, a liquid material containing a polymerizable monomer having an acidic group, a polymerizable monomer having no acidic group, a specific basic compound, and water and exhibiting a pH in a specific range, and further containing a chemical polymerization initiator in the powder material and / or the liquid material, has excellent adhesion to tooth structure and storage stability, and is useful for bonding fillings and restorations and prosthetics.
[0004] The operation of attaching a dental prosthesis to a tooth using this resin-reinforced glass ionomer cement for dental bonding is performed by applying a mixture of cement to the adhesive surface of the dental prosthesis and then pressing the dental prosthesis against the tooth. At this time, the mixture is applied in an amount greater than the required amount so that it spreads over the entire adhesive interface between the dental prosthesis and the tooth. Therefore, when the dental prosthesis is pressed against the tooth, the excess mixture protrudes from the joint between the dental prosthesis and the tooth. This excess mixture is called excess cement, and when it hardens to a certain extent and becomes semi-hardened, it is removed with a sharp-tipped instrument called a dental probe.
[0005] In addition, when the dental prosthesis is a crown or bridge, the joint between the dental prosthesis and the tooth (hereinafter referred to as the margin) is near the gingival margin or below the gingival margin on the tooth surface, so when removing the excess cement, it is necessary to pay close attention not to damage the surrounding gums with a dental probe. In particular, removing the excess cement from the adjacent surface between teeth is even more difficult. Therefore, in addition to the above-mentioned basic properties (adhesion to tooth structure, thin coating thickness), dental resin-reinforced glass ionomer cement is also required to be able to easily remove the excess cement. If the excess cement is not sufficiently removed, there is a concern that the risk of periodontitis will increase (Non-Patent Document 1). As such, the removability of the excess cement is an extremely important property because it greatly affects the prognosis. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2014-181190 A [Non-patent literature]
[0007] [Non-Patent Document 1] Thomas G. Wilson Jr.,J Periodontol 2009,80(9),1388-1392 Summary of the Invention [Problem to be solved by the invention]
[0008] As mentioned above, the excess cement is removed when it is in a semi-hardened state. This is because the excess cement can be easily removed without the need for strong force, and the risk of leaving it behind or damaging the gums is minimized. Therefore, the longer the excess cement is in a semi-hardened state during the hardening process, the more time is available for the removal work, which is preferable. In addition, if the semi-hardened excess cement has a tear-resistant property, it can be removed in one lump, which greatly reduces the burden of the work, which is more preferable. This tear-resistant property is particularly useful when removing excess cement from adjacent surfaces, where visibility is poor and there is a high risk of leaving excess cement behind.
[0009] Although conventional resin-reinforced glass ionomer cements for luting maintain a semi-cured state for a certain amount of time during the curing process, in cases where it takes a long time to remove excess cement, such as when removing excess cement from multiple teeth at once, the time to maintain the semi-cured state is insufficient. Also, when the thickness of the excess cement becomes thin, it can tear when it is removed, so there is a demand for a cement that is less likely to tear.
[0010] Therefore, an object of the present invention is to provide a resin-reinforced glass ionomer cement composition for dental bonding that can maintain a semi-hardened state for a longer period of time, at which time excess cement can be removed, is less likely to tear even when the excess cement is thin, and also has excellent adhesion to tooth structure, which is an important basic property of dental cement. [Means for solving the problem]
[0011] In view of the above-mentioned problems, the inventors have conducted intensive research and have discovered that the above-mentioned problems can be solved by providing a resin-reinforced glass ionomer cement composition for dental bonding which comprises a first agent containing an acid-reactive glass and a second agent containing a polyalkenoic acid and water, wherein at least one of the first agent and the second agent contains a polymerizable monomer, wherein the first agent contains an aryl borate compound as a polymerization initiator, and the content of polyalkenoic acid in the second agent and the ratio of polyalkenoic acid to water contained in the second agent are within specific ranges, thereby completing the present invention. That is, the above problems can be solved by using the following component configuration.
[0012] 1. A resin-reinforced glass ionomer cement composition for dental bonding comprising a first agent containing (a) an aryl borate compound and (b) an acid-reactive glass powder, and a second agent containing (c) a polyalkenoic acid and (d) water, wherein at least one of the first agent and the second agent contains (e) a polymerizable monomer, wherein the content of the polyalkenoic acid (c) contained in the second agent is in the range of more than 20% by mass and less than 70% by mass relative to the entire second agent, and when the sum of the polyalkenoic acid (c) contained in the second agent and the water (d) contained in the second agent is taken as 100% by mass, the content of the polyalkenoic acid (c) contained in the second agent is in the range of more than 45% by mass and less than 75% by mass. Effect of the Invention
[0013] The resin-reinforced glass ionomer cement composition for dental luting of the present invention not only exhibits excellent adhesion to tooth structure, but also maintains a semi-hardened state suitable for removing excess cement for a long period during the hardening process, allowing for ample removal of excess cement. Furthermore, since the excess cement is not easily torn off even when it becomes thin, it can be easily removed even from adjacent surfaces between teeth where removal is difficult. This reduces the risk of developing periodontitis due to excess cement being left behind. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] As used herein, the term "polyalkenoic acid" refers to a polymer containing ethylenically unsaturated monomer units having an acidic group. In this specification, (meth)acrylate refers to both acrylate and methacrylate, (meth)acryloyl refers to both acryloyl and methacryloyl, and (meth)acrylamide refers to acrylamide and methacrylamide inclusively.
[0015] The resin-reinforced glass ionomer cement composition for dental bonding of the present invention comprises a first agent containing (a) an aryl borate compound and (b) an acid-reactive glass powder, and a second agent containing (c) a polyalkenoic acid and (d) water, and at least one of the first agent and the second agent contains (e) a polymerizable monomer, characterized in that the content of the polyalkenoic acid (c) contained in the second agent relative to the entire second agent is in the range of more than 20% by mass and less than 70% by mass, and the content of the polyalkenoic acid (c) contained in the second agent in a total of 100 parts by mass of the polyalkenoic acid (c) contained in the second agent and the water (d) contained in the second agent is in the range of more than 45 parts by mass and less than 75 parts by mass. This component composition exhibits excellent adhesion to tooth structure and maintains a semi-hardened state suitable for removing excess cement for a long period during the hardening process. At the same time, the excess cement in this semi-hardened state is less likely to tear apart, allowing the excess cement to be easily removed from the margins.
[0016] The present invention will be described in detail below. The (a) aryl borate compound that can be used in the resin-reinforced glass ionomer cement composition for dental bonding of the present invention is an organic boron compound having three or four aryl groups in one molecule, represented by the following general formula (1).
[0017] [Formula (1)] [ka] [In the formula, R1 represents an alkyl group, an aryl group, or an alkenyl group, each of which may have a substituent, and R2 to R7 each independently represent a hydrogen atom, a halogen atom, a nitro group, or an alkyl group, a phenyl group, or an alkoxy group, each of which may have a substituent. + represents an alkali metal ion, a tertiary or quaternary ammonium ion, a quaternary pyridinium ion, a quaternary quinolinium ion, or a quaternary phosphonium ion.
[0018] Specific examples of the aryl borate compound (a) represented by the above formula (1) are given below. Examples of borate compounds having three aryl groups in one molecule include monoalkyltriphenylboron, monoalkyltris(p-chlorophenyl)boron, monoalkyltris(p-fluorophenyl)boron, monoalkyltris[3,5-bis(trifluoromethyl)phenyl]boron, monoalkyltris[3,5-bis(1,1,1,3,3,3-hexafluoro-2-methoxy-2-propyl)phenyl]boron, monoalkyltris(p-nitrophenyl)boron, monoalkyltris(m-nitrophenyl)boron, monoalkyltris(p-butylphenyl)boron, monoalkyltris(m-butylphenyl)boron, and monoalkyltris(p-butyl). Examples of the alkyl group include, but are not limited to, sodium salts, lithium salts, potassium salts, tetrabutylammonium salts, tetramethylammonium salts, tetraethylammonium salts, tributylamine salts, triethanolamine salts, methylpyridinium salts, ethylpyridinium salts, butylpyridinium salts, methylquinolinium salts, ethylquinolinium salts, and butylquinolinium salts of monoalkyltris(m-butyloxyphenyl)boron, monoalkyltris(p-octyloxyphenyl)boron, and monoalkyltris(m-octyloxyphenyl)boron (the alkyl group is an n-butyl group, an n-octyl group, an n-dodecyl group, and the like).
[0019] Examples of borate compounds having four aryl groups in one molecule include tetraphenylboron, tetrakis(p-chlorophenyl)boron, tetrakis(p-fluorophenyl)boron, tetrakis[3,5-bis(trifluoromethyl)phenyl]boron, tetrakis[3,5-bis(1,1,1,3,3,3-hexafluoro-2-methoxy-2-propyl)phenyl]boron, tetrakis(p-nitrophenyl)boron, tetrakis(m-nitrophenyl)boron, tetrakis(p-butylphenyl)boron, tetrakis(m-butylphenyl)boron, and tetrakis(p-butylphenyl)boron. Examples of suitable cation exchange salts include, but are not limited to, sodium salts, lithium salts, potassium salts, tetrakis(m-butyloxyphenyl)boron, tetrakis(p-octyloxyphenyl)boron, tetrakis(m-octyloxyphenyl)boron, tetrabutylammonium salts, tetramethylammonium salts, tetraethylammonium salts, tributylamine salts, triethanolamine salts, methylpyridinium salts, ethylpyridinium salts, butylpyridinium salts, methylquinolinium salts, ethylquinolinium salts, and butylquinolinium salts of tetrakis(m-octyloxyphenyl)boron.
[0020] These (a) aryl borate compounds can be used alone or in combination of two or more kinds. The resin-reinforced glass ionomer cement composition for dental bonding of the present invention can contain no aryl borate compounds other than the organoboron compound having three or four aryl groups in one molecule.
[0021] The (a) aryl borate compound is preferably contained in an amount of 0.01% by mass to 30% by mass, more preferably 0.1% by mass to 25% by mass, based on the total amount of the (e) polymerizable monomer. If the content of the (a) aryl borate compound is less than 0.01% by mass, the curability may deteriorate and the mechanical properties may decrease. If the content of the (a) aryl borate compound is more than 30% by mass, the storage stability may deteriorate.
[0022] The (b) acid-reactive glass powder that can be used in the dental resin-reinforced glass ionomer cement composition of the present invention must contain an acid-reactive element such as a metal element, and a fluorine element. The (b) acid-reactive glass powder contains an acid-reactive element, and in the presence of (d) water, an acid-base reaction with the acidic group of the (c) polyalkenoic acid proceeds. Specific examples of the acid-reactive element include, but are not limited to, sodium, potassium, calcium, strontium, barium, lanthanum, aluminum, zinc, etc. These acid-reactive elements may be contained in one or more types, and the content of these elements is not particularly limited.
[0023] Furthermore, in order to impart X-ray contrast to the resin-reinforced glass ionomer cement composition for dental bonding of the present invention, it is preferable that the acid-reactive glass powder (b) contains an element that is opaque to radioactivity. Specific examples of the element that is opaque to radioactivity include, but are not limited to, strontium, lanthanum, zirconium, titanium, yttrium, ytterbium, tantalum, tin, tellurium, tungsten, and bismuth. In addition, there is no particular restriction on other elements contained in the acid-reactive glass powder (b), and the acid-reactive glass powder (b) of the present invention can contain various elements.
[0024] (b) Examples of acid-reactive glass powders include aluminosilicate glass, borosilicate glass, aluminoborate glass, boroaluminosilicate glass, phosphate glass, borate glass, and silica glass, which contain the above-mentioned acid-reactive elements, fluorine, and X-ray opaque elements, but are not limited to these.
[0025] Furthermore, the particle shape of the (b) acid-reactive glass powder is not particularly limited, and any particle shape such as spherical, needle-like, plate-like, crushed, scale-like, etc. can be used without any restrictions. These (b) acid-reactive glass powders can be used alone or in combination of several kinds.
[0026] The method for producing these (b) acid-reactive glass powders is not particularly limited, and any of the methods such as a melting method, a gas phase method, and a sol-gel method can be used. Among these, it is preferable to use the (b) acid-reactive glass powder produced by the melting method or the sol-gel method, which are easy to control the type and content of elements.
[0027] (b) The acid-reactive glass powder can be used after being pulverized to a desired particle size. The pulverization method is not particularly limited, and either wet or dry pulverization can be used. Specifically, the glass powder can be pulverized using a high-speed rotary mill such as a hammer mill or turbo mill, a container-driven mill such as a ball mill, planetary mill or vibration mill, a media-agitating mill such as an attritor or bead mill, or a jet mill, etc., to appropriately adjust the particle size according to the desired properties to be imparted to the resin-reinforced glass ionomer cement composition for dental bonding of the present invention.
[0028] In the resin-reinforced glass ionomer cement composition for dental bonding of the present invention, in order to achieve a thin coating thickness, the 50% particle size (D50) of the acid-reactive glass powder (b) is preferably 0.1 μm or more and 30 μm or less, and more preferably 0.1 μm or more and 10 μm or less. Here, the "50% particle size (D50)" refers to the particle size at which the cumulative value from the small particle size side is 50% in the volume-based particle size distribution measured using a laser diffraction / scattering particle size distribution measuring device or the like.
[0029] If the 50% particle size (D50) of the (b) acid-reactive glass powder is less than 0.1 μm, the surface area increases and it becomes impossible to include a large amount in the composition, which may result in a decrease in mechanical properties and a shortened operation time. If the 50% particle size (D50) of the (b) acid-reactive glass powder exceeds 30 μm, the coating thickness becomes thick, and the cemented and / or bonded dental prosthetic device may lift up, causing discomfort in occlusion. The resin-reinforced glass ionomer cement composition for dental bonding of the present invention can contain only acid-reactive glass powder having a particle size (D50) of 0.1 μm or more and 30 μm or less as the (b) acid-reactive glass powder.
[0030] In order to adjust the operability, hardening characteristics, mechanical characteristics, etc. of the resin-reinforced glass ionomer cement composition for dental bonding of the present invention, the (b) acid-reactive glass powder can be subjected to various surface treatments, heat treatments, or agglomeration treatments in the liquid phase or gas phase, etc., within the scope of not adversely affecting the acid-base reaction with the (c) polyalkenoic acid. Moreover, these treatments can be performed alone or in combination of several types, and the order of each treatment is not particularly limited. Among these, surface treatments or heat treatments are preferred because they are easy to control various properties and have excellent productivity.
[0031] Specific examples of the surface treatment of the (b) acid-reactive glass powder include washing with an acid such as phosphoric acid or acetic acid, surface treatment with an acidic compound such as tartaric acid or polycarboxylic acid, surface treatment with a fluoride such as aluminum fluoride, and surface treatment with a silane compound such as (meth)acryloyloxymethyltrimethoxysilane, 3-(meth)acryloyloxypropyltrimethoxysilane, 8-(meth)acryloyloxyoctyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, tetramethoxysilane, tetraethoxysilane, partially hydrolyzed oligomer of tetramethoxysilane, and partially hydrolyzed oligomer of tetraethoxysilane. The surface treatments that can be used in the present invention are not limited to those described above, and these surface treatments can be used alone or in combination. Furthermore, there is no particular restriction on the amount of the surface treatment agent relative to the (b) acid-reactive glass powder when performing the surface treatment, and it may be appropriately adjusted according to the particle size of the (b) acid-reactive glass powder and the desired properties.
[0032] (b) A specific example of the heat treatment of the acid-reactive glass powder is a treatment method in which the powder is heated in an electric furnace or the like at a temperature in the range of 200° C. to 800° C. for 1 hour to 72 hours. The heat treatments that can be used in the present invention are not limited to those described above, and the treatment process can also be a treatment at a single temperature or a multi-stage treatment at multiple temperatures.
[0033] The content of the (b) acid-reactive glass powder is preferably 30% by mass or more and 75% by mass or less, more preferably 32% by mass or more and 73% by mass or less, based on the total resin-reinforced glass ionomer cement composition for dental bonding of the present invention. If the content of the (b) acid-reactive glass powder is less than 30% by mass, the hardening may be delayed or the mechanical properties may be deteriorated. If the content of the (b) acid-reactive glass powder is more than 75% by mass, the kneaded product may become too hard and the coating thickness may become thick, and the bonded and / or adhered dental prosthetic device may lift up, causing discomfort in the bite.
[0034] The (c) polyalkenoic acid that can be used in the dental resin-reinforced glass ionomer cement composition of the present invention can be any homopolymer or copolymer of an ethylenically unsaturated monomer having at least one acidic group such as a carboxy group, a phosphate group, a phosphonic acid group, or a sulfonic acid group in the molecule, such as an ethylenically unsaturated monocarboxylic acid, an ethylenically unsaturated dicarboxylic acid, an ethylenically unsaturated tricarboxylic acid, an ethylenically unsaturated phosphoric acid, an ethylenically unsaturated phosphonic acid, or an ethylenically unsaturated sulfonic acid, without any limitation. Furthermore, the (c) polyalkenoic acid can be a copolymer of an ethylenically unsaturated monomer that does not have an acidic group in the molecule and an ethylenically unsaturated monomer that has an acidic group. Among them, it is more preferable that the acidic group of the (c) polyalkenoic acid is a carboxy group, since it is easy to obtain good adhesion to tooth structure and high mechanical properties. In this specification, "the acidic groups of the (c) polyalkenoic acid are carboxy groups" means that 60% or more, preferably 70% or more, and more preferably 80% or more of the acidic groups of the (c) polyalkenoic acid are carboxy groups. The resin-reinforced glass ionomer cement composition for dental bonding of the present invention can contain only (c) polyalkenoic acid whose acidic groups are carboxy groups as the (c) polyalkenoic acid.
[0035] Specific examples of ethylenically unsaturated monomers having an acidic group that can be used to obtain the (c) polyalkenoic acid include ethylenically unsaturated monocarboxylic acids such as (meth)acrylic acid, 2-chloroacrylic acid, 3-chloroacrylic acid, and 2-cyanoacrylic acid; ethylenically unsaturated dicarboxylic acids such as mesaconic acid, maleic acid, maleic anhydride, itaconic acid, itaconic anhydride, fumaric acid, glutaconic acid, and citraconic acid; ethylenically unsaturated tricarboxylic acids such as aconitic acid, 1-butene-1,2,4-tricarboxylic acid, and 3-butene-1,2,3-tricarboxylic acid; 2-(meth)acryloyloxyethyl phosphate, 2-(meth)acryloyloxyethyl phenyl phosphate, 2-(meth)acryloyloxyethyl phenyl-2-bromoethyl phosphate, 10-(meth)acryloyloxydecyl dihydrogen phosphate, 12-(meth)acryloyloxyethyl phenyl phosphate, 10-(meth)acryloyloxydecyl dihydrogen phosphate, 12-(meth)acryloyloxyethyl phenyl phosphate, 10-(meth)acryloyloxyethyl ... ethylenically unsaturated phosphoric acids such as 5-(meth)acryloyloxypentyl-3-phosphonopropionate, 6-(meth)acryloyloxyhexyl-3-phosphonopropionate, 10-(meth)acryloyloxydecyl-3-phosphonopropionate, 6-(meth)acryloyloxyhexyl-3-phosphonoacetate, 10-(meth)acryloyloxydecyl-3-phosphonoacetate, and the like; ethylenically unsaturated phosphonic acids such as vinyl sulfonic acid, 2-(meth)acrylamido-2-methylpropanesulfonic acid, 2-sulfoethyl (meth)acrylate, allyl sulfonic acid, methallyl sulfonic acid, methallyl oxybenzenesulfonic acid, allyloxybenzenesulfonic acid, and styrenesulfonic acid, but are not limited thereto.
[0036] The polymerization method used to obtain various (c) polyalkenoic acids is not particularly limited, and any method such as solution polymerization, suspension polymerization, emulsion polymerization, etc. can be used without any restrictions. In addition, known polymerization initiators and chain transfer agents can be used during the synthesis of the polymer, and the amounts of these additives can be appropriately adjusted to obtain the desired polymer. The (c) polyalkenoic acids thus obtained can be used alone or in combination.
[0037] The weight-average molecular weight of the (c) polyalkenoic acid is preferably in the range of 3,000 to 300,000. Here, the weight-average molecular weight is the average molecular weight calculated based on the molecular weight distribution measured by gel permeation chromatography. If the weight-average molecular weight of the (c) polyalkenoic acid is less than 3,000, the removability of excess cement, the adhesive strength, or the mechanical properties may be reduced. If the weight-average molecular weight of the (c) polyalkenoic acid is more than 300,000, the removability of excess cement may be reduced, the operation time may be shortened, or the viscosity of the kneaded product may increase, resulting in poor kneading, making it difficult to obtain a uniform kneaded product, and the mechanical properties may be reduced. The resin-reinforced glass ionomer cement composition for dental luting of the present invention can contain only the (c) polyalkenoic acid having a weight-average molecular weight in the range of 3,000 to 300,000 as the (c) polyalkenoic acid.
[0038] In addition, (c) polyalkenoic acid can be used after neutralizing some of its acidic groups with a basic compound in order to adjust the acid-base reactivity with (b) acid-reactive glass powder, so long as it does not adversely affect various properties. Examples of basic compounds used for neutralization include alkali metal hydroxides such as sodium hydroxide, potassium hydroxide, and lithium hydroxide, alkali metal carbonates such as sodium carbonate, potassium carbonate, and lithium carbonate, and alkali metal bicarbonates such as sodium bicarbonate, potassium bicarbonate, and lithium bicarbonate. In addition, various amine compounds such as primary amines, secondary amines, and tertiary amines can be used without any problem, so long as they can maintain solubility in water after neutralization. As the amine compound, triethanolamine, diethanolamine, methyldiethanolamine, 2-dimethylaminoethyl (meth)acrylate, etc. can be suitably used.
[0039] The content of (c) polyalkenoic acid in the second agent must be in the range of more than 20% by mass and less than 70% by mass, preferably more than 25% by mass and less than 65% by mass, based on the total amount of the second agent of the resin-reinforced glass ionomer cement composition for dental bonding of the present invention. If the content of (c) polyalkenoic acid is less than 20% by mass, the adhesion to tooth structure and the removability of excess cement are reduced. If the content of (c) polyalkenoic acid is more than 70% by mass, the adhesion to tooth structure is reduced.
[0040] In addition, when the total of the (c) polyalkenoic acid contained in the second agent of the dental resin-reinforced glass ionomer cement composition of the present invention and the (d) water contained in the second agent described below is taken as 100% by mass, the content of the (c) polyalkenoic acid contained in the second agent must be in the range of more than 45% by mass and less than 75% by mass, preferably more than 50% by mass and less than 75% by mass, and more preferably more than 52.5% by mass and less than 75% by mass. If the content of the (c) polyalkenoic acid is 45% by mass or less, the adhesion to the tooth structure and the removability of the excess cement are reduced. If the content of the (c) polyalkenoic acid is 75% by mass or more, the adhesion to the tooth structure and the removability of the excess cement are reduced.
[0041] (d) Water that can be used in the resin-reinforced glass ionomer cement composition for dental bonding of the present invention functions as a solvent for dissolving (c) polyalkenoic acid, and is also a component for diffusing metal ions eluted from (b) acid-reactive glass powder and inducing a crosslinking reaction with (c) polyalkenoic acid.
[0042] (d) Water may be used without any restrictions so long as it does not contain impurities that inhibit the acid-base reaction in the dental resin-reinforced glass ionomer cement composition of the present invention or that adversely affect the hardening properties or mechanical properties. However, it is preferable to use distilled water or ion-exchanged water.
[0043] The content of (d) water is preferably 6% by mass or more and 50% by mass or less of the total resin-reinforced glass ionomer cement composition for dental bonding of the present invention. If the content of (d) water is less than 6% by mass or if the content of (d) water is more than 50% by mass, the hardening property or mechanical properties may decrease.
[0044] The polymerizable monomer (e) that can be used in the dental resin-reinforced glass ionomer cement composition of the present invention is not particularly limited in its molecular structure, and any known polymerizable monomer can be used. That is, the polymerizable unsaturated group of the polymerizable monomer (e) includes, but is not limited to, a (meth)acryloyloxy group, a (meth)acrylamide group, a styryl group, a vinyl group, an allyl group, and the like. Among these polymerizable unsaturated groups, a (meth)acryloyloxy group or a (meth)acrylamide group is preferable because of its excellent polymerization rate. In addition, the number of polymerizable unsaturated groups of the polymerizable monomer (e) is also not particularly limited. The hydrocarbon group bonded to the polymerizable unsaturated group may be any of an aliphatic hydrocarbon group, an alicyclic hydrocarbon group, an aromatic hydrocarbon group, and a combination thereof, and the hydrocarbon group may have any substituent such as an acidic group, a hydroxyl group, a halogen atom, an alkoxy group, an amino group, or a glycidyl group. Specific examples of the polymerizable monomer (e) are shown below, but are not limited to these. These may be used alone or in combination of two or more.
[0045] Examples of monofunctional polymerizable monomers include (meth)acrylic acid, methyl (meth)acrylate, ethyl (meth)acrylate, isopropyl (meth)acrylate, n-propyl (meth)acrylate, isobutyl (meth)acrylate, n-butyl (meth)acrylate, t-butyl (meth)acrylate, sec-butyl (meth)acrylate, n-amyl (meth)acrylate, isoamyl (meth)acrylate, n-hexyl (meth)acrylate, isodecyl (meth)acrylate, lauryl (meth)acrylate, and stearyl (meth)acrylate. , 2-ethylhexyl (meth)acrylate, cyclohexyl (meth)acrylate, adamantyl (meth)acrylate, phenyl (meth)acrylate, benzyl (meth)acrylate, 2-phenylethyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, glycidyl (meth)acrylate, isobornyl (meth)acrylate, allyl (meth)acrylate, 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, phenoxyethyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate ) acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, glycerol (meth)acrylate, (meth)acryloyloxyethyl methyl succinate, 2-(meth)acryloyloxyethyl propionate, acetoacetoxyethyl (meth)acrylate, acetoacetoxypropyl (meth)acrylate, acetoacetoxybutyl (meth)acrylate and other (meth)acrylic acid esters, γ-(meth)acryloyloxypropyl trimethacrylate Examples of suitable silane compounds include silane compounds such as oxysilane and γ-(meth)acryloyloxypropyltriethoxysilane; amines such as 2-(N,N-dimethylamino)ethyl (meth)acrylate and 2-(N,N-diethylamino)ethyl (meth)acrylate; fluorine-containing (meth)acrylates such as 2,2,2-trifluoroethyl (meth)acrylate, perfluorohexylethyl (meth)acrylate and perfluorooctylethyl (meth)acrylate; and (meth)acrylamides thereof, as well as N-methylol (meth)acrylamide.
[0046] Examples of aromatic bifunctional polymerizable monomers include 2,2-bis[4-[3-(meth)acryloyloxy-2-hydroxypropoxy]phenyl]propane, 2,2-bis(4-(meth)acryloyloxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxyethoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxydiethoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxytetraethoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxypentaethoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxydipropoxyphenyl)propane, 2(4-(meth)acryloyloxyethoxyphenyl)- ... 2(4-(meth)acryloyloxydiethoxyphenyl)propane, 2(4-(meth)acryloyloxytriethoxyphenyl)propane, 2(4-(meth)acryloyloxydipropoxyphenyl)-2(4-(meth)acryloyloxytriethoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxydipropoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxyisopropoxyphenyl)propane, 2,2-bis(4-(meth)acryloyloxypolyethoxyphenyl)propane, 9,9-bis[4-(2-(meth)acryloyloxyethoxy)phenyl]fluorene, and (meth)acrylamides thereof.
[0047] Examples of the aliphatic bifunctional polymerizable monomer include ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 3-methyl-1,5-pentanediol di(meth)acrylate, 1,3-butanediol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, and the like. Examples of the acrylates include ol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, 2-hydroxypropyl-1,3-di(meth)acrylate, 3-hydroxypropyl-1,2-di(meth)acrylate, 2-hydroxy-3-acryloyloxypropyl (meth)acrylate, 1,2-bis(3-(meth)acryloyloxy-2-hydroxypropoxy)ethane, 1,2-bis(3-(meth)acryloyloxy-2-hydroxypropoxy)propane, 2-hydroxy-1,3-bis(3-(meth)acryloyloxy-2-hydroxypropoxy)propane, and (meth)acrylamides thereof.
[0048] Examples of the trifunctional or higher polymerizable monomer include trimethylolpropane tri(meth)acrylate, trimethylolethane tri(meth)acrylate, trimethylolmethane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, glycerin tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, and (meth)acrylamides thereof.
[0049] Examples of the urethane-based polymerizable monomer include (meth)acrylate compounds having a urethane bond derived from an adduct of a polymerizable monomer having a hydroxyl group, such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-chloro-2-hydroxypropyl (meth)acrylate, and an isocyanate compound, such as methylcyclohexane diisocyanate, methylene bis(4-cyclohexyl isocyanate), hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, isophorone diisocyanate, diisocyanate methylmethylbenzene, and 4,4-diphenylmethane diisocyanate.
[0050] The content of the (e) polymerizable monomer is preferably 1% by mass or more and 70% by mass or less, and more preferably 2.5% by mass or more and 60% by mass or less, based on the total mass of the resin-reinforced glass ionomer cement composition for dental bonding of the present invention. If the content of the (e) polymerizable monomer is less than 1% by mass or if the content of the (e) polymerizable monomer is more than 70% by mass, the hardening property or the mechanical properties may decrease.
[0051] Furthermore, it is preferable that the (e) polymerizable monomer contains a water-soluble polymerizable monomer. When the composition contains a water-soluble polymerizable monomer, the wettability of the composition to tooth structure may be improved, and the adhesiveness to tooth structure may be improved.
[0052] In the present invention, the water-soluble polymerizable monomer means a compound having a solubility of 5 parts by mass or more in 100 g of water at 25° C. and having at least one polymerizable unsaturated group. As the water-soluble polymerizable monomer, those having a hydrophilic group such as a hydroxyl group, an oxymethylene group, an oxyethylene group, an oxypropylene group, or an amide group are preferable.
[0053] Specific examples of water-soluble polymerizable monomers include (meth)acrylic acid, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 1,3-dihydroxypropyl (meth)acrylate, 2,3-dihydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 2-((meth)acryloyloxy)ethyltrimethylammonium chloride, 3-chloro-2-hydroxypropyl (meth)acrylate, polyethylene glycol di(meth)acrylate (containing 9 or more ethyleneoxy groups), 2-hydroxy-3-acryloyloxypropyl (meth)acrylate, and glycerol 1,3-dimethacrylate. Examples of the acrylamide include, but are not limited to, acrylate, N-methylol (meth)acrylamide, N-hydroxyethyl (meth)acrylamide, N,N-bis(2-hydroxyethyl) (meth)acrylamide, N-methoxymethyl (meth)acrylamide, N-ethoxymethyl (meth)acrylamide, diacetone (meth)acrylamide, 4-(meth)acryloylmorpholine, N-trihydroxymethyl-N-methyl (meth)acrylamide, N,N-bis(2-acrylamidoethyl)acrylamide, N,N'-1,2-ethanediylbis{N-[2-(acryloylamino)ethyl]acrylamide}, and N-[tris(3-acrylamidopropoxymethyl)methyl]acrylamide. These may be used alone or in combination of two or more.
[0054] The water-soluble polymerizable monomer is preferably contained in an amount of 10% by mass or more and 97.5% by mass or less, more preferably 20% by mass or more and 95% by mass or less, based on the total amount of the (e) polymerizable monomer. If the content of the water-soluble polymerizable monomer is less than 10% by mass, the effect of improving adhesion to tooth structure may not be sufficiently obtained. Also, if the content of the water-soluble polymerizable monomer is more than 97.5% by mass, the mechanical properties may be reduced.
[0055] The resin-reinforced glass ionomer cement composition for dental luting of the present invention may contain (f) an acidic component having a molecular weight of 500 or less in order to prolong the time of maintaining a semi-cured state suitable for removing excess cement. Here, the (f) acidic component having a molecular weight of 500 or less means a compound having an acidic group such as a carboxy group, a phosphoric acid group, a phosphonic acid group, or a sulfonic acid group in the molecule and having a molecular weight of 500 or less. Among these (f) acidic components having a molecular weight of 500 or less, a compound having an acidic group of a carboxy group is preferred, and a compound having two or more carboxy groups is more preferred. The resin-reinforced glass ionomer cement composition for dental luting of the present invention may contain only a compound having an acidic group of a carboxy group as the (f) acidic component having a molecular weight of 500 or less, and may contain only a compound having two or more carboxy groups. In addition, it is more preferred that the (f) acidic component having a molecular weight of 500 or less is a compound having no polymerizable group. The resin-reinforced glass ionomer cement composition for dental luting of the present invention may contain only a compound having no polymerizable group as the (f) acidic component having a molecular weight of 500 or less.
[0056] (f) Specific examples of acidic components having a molecular weight of 500 or less include carboxylic acid compounds such as acetic acid, propionic acid, (meth)acrylic acid, 2-chloroacrylic acid, 3-chloroacrylic acid, tartaric acid, mesaconic acid, itaconic acid, maleic acid, fumaric acid, glutaconic acid, citraconic acid, citric acid, malic acid, aconitic acid, tricarballylic acid, 1-butene-1,2,4-tricarboxylic acid, 3-butene-1,2,3-tricarboxylic acid, and 4-(meth)acryloyloxyethyl trimellitic acid, phosphoric acid, pyrophosphoric acid, tripolyphosphoric acid, 2-(meth)acryloyloxyethyl phosphoric acid, 2-(meth)acryloyloxyethyl phenyl phosphoric acid, 10-(meth)acryloyloxydecyl dihydrogen phosphate, and 12-(meth)acryloyloxydecyl dihydrogen phosphate. Examples of the acidic component include, but are not limited to, phosphoric acid compounds such as decyl dihydrogen phosphate, phosphonic acid, methyl phosphonic acid, 5-(meth)acryloyloxypentyl phosphonopropionate, 6-(meth)acryloyloxyhexyl phosphonopropionate, 10-(meth)acryloyloxydecyl phosphonopropionate, 6-(meth)acryloyloxyhexyl phosphonoacetate, and 10-(meth)acryloyloxydecyl phosphonoacetate, and sulfonic acid compounds such as vinyl sulfonic acid, allyl sulfonic acid, 2-(meth)acrylamido-2-methylpropanesulfonic acid, 2-sulfoethyl (meth)acrylate, alkylbenzenesulfonic acid, and styrenesulfonic acid. In addition, these (f) acidic components having a molecular weight of 500 or less can be used alone or in combination.
[0057] The (f) acidic component having a molecular weight of 500 or less is preferably contained in the range of 0.1% by mass to 20% by mass based on the total amount of the resin-reinforced glass ionomer cement composition for dental luting of the present invention. If the content of the (f) acidic component having a molecular weight of 500 or less is less than 0.1% by mass, the time for maintaining the semi-cured state may not be sufficiently extended. If the content of the (f) acidic component having a molecular weight of 500 or less exceeds 20% by mass, the mechanical properties and adhesiveness to tooth structure may be reduced.
[0058] The dental resin-reinforced glass ionomer cement composition for bonding of the present invention may contain a chemical polymerization initiator other than the aryl borate compound (a) as long as the effect of the present invention is not impaired.
[0059] Specific examples of (a) chemical polymerization initiators other than aryl borate compounds include, but are not limited to, peroxide / amine compound, peroxide / amine compound / aromatic sulfinic acid or its salt, or aromatic sulfonyl compound, peroxide / amine compound / (thio)barbituric acid compound or (thio)barbiturate compound, peroxide / ascorbic acid compound, peroxide / thiourea / vanadium compound or copper compound, (thio)barbituric acid compound / organometallic compound / organohalogen compound, aromatic sulfinate salts that initiate polymerization by the action of an acidic compound, or a system combining a (thio)barbiturate salt and an acidic compound, and further organoboron compounds that initiate polymerization by reacting with oxygen or water.
[0060] Examples of peroxides include sodium peroxodisulfate, potassium peroxodisulfate, ammonium peroxodisulfate, sodium peroxodiphosphate, potassium peroxodiphosphate, ammonium peroxodiphosphate, diacyl peroxides, alkyl peroxy esters, peroxydicarbonates, monoperoxycarbonates, peroxyketals, dialkyl peroxides, hydroperoxides, and ketone peroxides. More specific examples of the peroxide include benzoyl peroxide, p-chlorobenzoyl peroxide, 2,4-dichlorobenzoyl peroxide, diacetyl peroxide, lauroyl peroxide, di-t-butyl peroxide, dicumyl peroxide, cumene hydroperoxide, t-butyl hydroperoxide, 1,1,3,3-tetramethylbutyl hydroperoxide, t-amyl hydroperoxide, isopropylbenzene hydroperoxide, 5-phenyl-4-pentenyl hydroperoxide, t-butylperoxyisopropyl carbonate, methyl ethyl ketone peroxide, 1,1-bis(t-butylperoxy)cyclohexane, 1,1-bis(t-hexylperoxy)cyclohexane, and t-butyl peroxybenzoate, but are not limited thereto.
[0061] The amine compound is preferably an aromatic secondary or aromatic tertiary amine, and specific examples thereof include N-methyl-p-toluidine, N-ethyl-p-toluidine, N-(2-hydroxyethyl)-p-toluidine, ethyl p-methylaminobenzoate, N-methylaniline, N-ethylaniline, N-(2-hydroxyethyl)aniline, N,N-dimethylaniline, N,N-diethylaniline, N,N-bis(2-hydroxyethyl)aniline, N-(2-hydroxyethyl)-N-methylaniline, N-ethyl-N-(2-hydroxyethyl)aniline, N,N-dimethyl-p-toluidine, N,N-diethyl-p-toluidine, N,N-bis(2-hydroxyethyl)-p-toluidine, ethyl p-dimethylaminobenzoate, and the like, but are not limited thereto.
[0062] Examples of aromatic sulfinic acids or salts thereof, or aromatic sulfonyl compounds include benzenesulfinic acid, p-toluenesulfinic acid, o-toluenesulfinic acid, 2,4,6-trimethylbenzenesulfinic acid, 2,4,6-triisopropylbenzenesulfinic acid, and sodium salts, potassium salts, lithium salts, or ammonium salts thereof, or benzenesulfonyl chloride, benzenesulfonyl fluoride, benzenesulfonamide, benzenesulfonyl hydrazide, p-toluenesulfonyl chloride, p-toluenesulfonyl fluoride, p-toluenesulfonamide, p-toluenesulfonyl hydrazide, and the like, but are not limited thereto.
[0063] Examples of (thio)barbituric acid compounds or (thio)barbiturate compounds include barbituric acid, 1,3-dimethylbarbituric acid, 1,3-diphenylbarbituric acid, 1,5-dimethylbarbituric acid, 5-butylbarbituric acid, 5-ethylbarbituric acid, 5-isopropylbarbituric acid, 5-cyclohexylbarbituric acid, 5-laurylbarbituric acid, 1,3,5-trimethylbarbituric acid, 1,3-dimethyl-5-ethylbarbituric acid, 1,3-dimethyl-n-butylbarbituric acid, 1,3-dimethyl-5-isobutylbarbituric acid, 1,3-dimethyl-5-cyclohexylbarbituric acid, and the like. Examples of barbituric acid include, but are not limited to, sylbarbituric acid, 1,3-dimethyl-5-phenylbarbituric acid, 1-cyclohexyl-5-ethylbarbituric acid, 1-phenyl-5-benzylbarbituric acid, 1-benzyl-5-phenylbarbituric acid, thiobarbituric acid, 1,3-dimethylthiobarbituric acid, 5-phenylthiobarbituric acid, and their alkali metal salts (lithium, sodium, potassium salts, etc.), alkaline earth metal salts (calcium, strontium, barium salts, etc.), ammonium salts, tetramethylammonium salts, and tetraethylammonium salts.
[0064] Examples of ascorbic acid compounds include, but are not limited to, L(+)-ascorbic acid, isoascorbic acid, sodium L(+)-ascorbate, potassium L(+)-ascorbate, calcium L(+)-ascorbate, sodium isoascorbate, and the like.
[0065] Examples of thiourea compounds include, but are not limited to, 1,3-dimethylthiourea, tetramethylthiourea, 1,1-diethylthiourea, 1,1,3,3-tetraethylthiourea, 1-allyl-2-thiourea, 1,3-diallylthiourea, 1,3-dibutylthiourea, 1,3-diphenyl-2-thiourea, 1,3-dicyclohexylthiourea, ethylenethiourea, N-methylthiourea, N-phenylthiourea, N-benzoylthiourea, and N-acetylthiourea.
[0066] Examples of vanadium compounds include, but are not limited to, vanadium acetylacetonate, vanadyl acetylacetonate, vanadyl stearate, vanadium naphthenate, vanadium benzoylacetonate, and the like.
[0067] Examples of copper compounds include, but are not limited to, copper acetate, copper salicylate, copper gluconate, copper oleate, copper benzoate, copper acetylacetonate, and copper naphthenate.
[0068] Examples of the organometallic compound include, in addition to the copper compounds, manganese acetylacetone, manganese naphthenate, manganese octoate, cobalt acetylacetone, cobalt naphthenate, lithium acetylacetone, lithium acetate, zinc acetylacetone, zinc naphthenate, nickel acetylacetone, nickel acetate, aluminum acetylacetone, calcium acetylacetone, iron acetylacetone, chromium acetylacetone, and sodium naphthenate, but are not limited to these.
[0069] Examples of organic halogen compounds include, but are not limited to, tetramethylammonium chloride, tetraethylammonium chloride, trioctylmethylammonium chloride, dilauryldimethylammonium chloride, lauryldimethylbenzylammonium chloride, tetra-n-butylammonium chloride, benzyldimethylcetylammonium chloride, and benzyldimethylstearylammonium chloride.
[0070] As the acidic compound to be reacted with aromatic sulfinates or (thio)barbiturates, both inorganic and organic acids can be used without any limitation, but it is preferable to use organic acids. Furthermore, from the viewpoint of the stability of the cured product, it is most preferable to use organic acids having a polymerizable group, that is, acidic group-containing polymerizable monomers. The acidic group-containing polymerizable monomer is not particularly limited in the type or number of polymerizable groups or acidic groups, and those generally used in the dental field can be used. Examples of acidic groups include carboxyl groups, phosphoric acid groups, phosphonic acid groups, and sulfonic acid groups. Representative acidic group-containing polymerizable monomers used in the dental field include, but are not limited to, 10-(meth)acryloyloxydecyl dihydrogen phosphate, 6-(meth)acryloyloxyhexyl-3-phosphonoacetate, 4-(meth)acryloyloxyethyl trimellitic acid and its anhydride, and 10-(meth)acryloyloxy-1,1-decanedicarboxylic acid. These acidic compounds can be used alone or in combination.
[0071] Examples of organic boron compounds that react with oxygen or water to initiate polymerization include trialkylborons such as triethylboron, tri(n-propyl)boron, triisopropylboron, tri(n-butyl)boron, tri(s-butyl)boron, triisobutylboron, tripentylboron, trihexylboron, and tricyclohexylboron, as well as partial oxides thereof, but are not limited to these.
[0072] When the resin-reinforced glass ionomer cement composition for dental bonding of the present invention contains a chemical polymerization initiator other than the aryl borate compound (a), the content of the chemical polymerization initiator is preferably 0.01% by mass to 20% by mass, more preferably 0.1% by mass to 15% by mass, based on the total amount of the polymerizable monomer (e). The resin-reinforced glass ionomer cement composition for dental bonding of the present invention may not contain a chemical polymerization initiator other than the aryl borate compound (a).
[0073] The resin-reinforced glass ionomer cement composition for dental bonding of the present invention may contain a photopolymerization initiator that initiates polymerization upon irradiation with ultraviolet or visible light.
[0074] Photopolymerization initiators that can be used in the resin-reinforced glass ionomer cement composition for dental bonding of the present invention include those made of a photosensitizer, and photosensitizer / photopolymerization accelerators.Specific examples of photosensitizers include α-diketones such as benzil, camphorquinone, α-naphthyl, acetonaphthene, p,p'-dimethoxybenzyl, p,p'-dichlorobenzylacetyl, pentanedione, 1,2-phenanthrenequinone, 1,4-phenanthrenequinone, 3,4-phenanthrenequinone, 9,10-phenanthrenequinone, and naphthoquinone; benzoin alkyl ethers such as benzoin, benzoin methyl ether, and benzoin ethyl ether; thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone, and 2-methylthioxanthone; Thioxanthones such as thioxanthone, 2-isopropylthioxanthone, 2-methoxythioxanthone, 2-hydroxythioxanthone, 2,4-diethylthioxanthone, and 2,4-diisopropylthioxanthone; benzophenone, p-chlorobenzophenone, p-methoxybenzophenone, and other benzophenones; 2,4,6-trimethylbenzoyldiphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, 2,6-dimethoxybenzoyldiphenylphosphine oxide, and other benzophenones; acylphosphine oxides such as bis(2,6-dimethoxybenzoyl)phenylphosphine oxide; α-aminoacetophenones such as 2-benzyl-dimethylamino-1-(4-morpholinophenyl)-butanone-1,2-benzyl-diethylamino-1-(4-morpholinophenyl)-propanone-1; ketals such as benzyl dimethyl ketal, benzyl diethyl ketal, and benzyl (2-methoxyethyl ketal); 3-(4-methoxybenzoyl)coumarin, 3-benzoyl-5,7-dimeth- coumarins such as 3,3'-oxycoumarin, 3,3'-carbonylbis(7-diethylaminocoumarin), and 3,3'-carbonylbis(7-dibutylaminocoumarin); titanocenes such as bis(cyclopentadienyl)-bis[2,6-difluoro-3-(1-pyrrolyl)phenyl]-titanium, bis(cyclopentadienyl)-bis(pentanefluorophenyl)-titanium, and bis(cyclopentadienyl)-bis(2,3,5,6-tetrafluoro-4-disiloxyphenyl)-titanium, but are not limited thereto.
[0075] Specific examples of the photopolymerization accelerator include N,N-dimethylaniline, N,N-diethylaniline, N,N-di-n-butylaniline, N,N-dibenzylaniline, N,N-dimethyl-p-toluidine, N,N-dimethyl-m-toluidine, N,N-diethyl-p-toluidine, p-bromo-N,N-dimethylaniline, m-chloro-N,N-dimethylaniline, p-dimethylaminobenzaldehyde, p-dimethylaminoacetophenone, p-dimethylaminobenzoic acid, ethyl p-dimethylaminobenzoate, isoamyl p-dimethylaminobenzoate, N,N-dimethylanthranilic acid methyl ester, N,N-dihydroxyethylaniline, N,N-dihydroxyethyl-p-toluidine, p-dimethylaminophenyl alcohol, p-dimethylaminostyrene, N,N-dimethyl-3,5-xylidine, 4-dimethylaminopyridine, N,N-dimethyl -α-naphthylamine, N,N-dimethyl-β-naphthylamine, triethanolamine, tributylamine, tripropylamine, triethylamine, N-methyldiethanolamine, N-ethyldiethanolamine, N,N-dimethylhexylamine, N,N-dimethyldodecylamine, N,N-dimethylstearylamine, N,N-dimethylaminoethyl (meth)acrylate, N,N-diethylaminoethyl (meth)acrylate, tertiary amines such as 2,2'-(n-butylimino)diethanol, secondary amines such as N-phenylglycine, barbituric acids such as 5-butylbarbituric acid, 1-benzyl-5-phenylbarbituric acid, 1,3,5-trimethylbarbituric acid, sodium 1,3,5-trimethylbarbiturate, and calcium 1,3,5-trimethylbarbiturate, 2,4,6-tris(trichloromethyl)-s-triazine, 2- Phenyl-4,6-bis(trichloromethyl)-s-triazine, 2-(p-chlorophenyl)-4,6-bis(trichloromethyl)-s-triazine, and 2-(4-biphenylyl)-4,Triazine compounds such as 6-bis(trichloromethyl)-s-triazine, diphenyliodonium chloride, diphenyliodonium hexafluorophosphate, diphenyliodonium hexafluoroantimonate, diphenyliodonium tetrafluoroborate, diphenyliodonium tetrakis(pentafluorophenyl)borate, bis-(4-methylphenyl)iodonium hexafluorophosphate, bis-(4-methylphenyl)iodonium hexafluoroantimonate, bis-(4-methylphenyl)iodonium tetrakis(pentafluorophenyl)borate, bis(4-tert-butylphenyl)iodonium hexafluoroantimonate, bis(4-tert-butylphenyl)iodonium hexafluoroantimonate, Examples of the dialkyl iodonium salts include diaryliodonium salts such as dibutyltin diacetate, dibutyltin dilaurate, dioctyltin dilaurate, dioctyltin diversatate, dioctyltin bis(mercaptoacetic acid isooctyl ester) salt, and tin compounds such as tetramethyl-1,3-diacetoxydistannoxane; aldehyde compounds such as lauryl aldehyde and terephthalaldehyde; and sulfur-containing compounds such as dodecyl mercaptan, 2-mercaptobenzoxazole, 1-decanethiol, and thiosalicylic acid, but are not limited to these.
[0076] Furthermore, in order to improve the photopolymerization promoting ability, in addition to the above photopolymerization accelerators, it is effective to add oxycarboxylic acids such as citric acid, malic acid, tartaric acid, glycolic acid, gluconic acid, α-oxyisobutyric acid, 2-hydroxypropanoic acid, 3-hydroxypropanoic acid, 3-hydroxybutanoic acid, 4-hydroxybutanoic acid, and dimethylolpropionic acid, but the addition is not limited to these.
[0077] These polymerization initiators can be used alone or in combination, regardless of the polymerization mode. Furthermore, these polymerization initiators can be subjected to secondary treatment such as encapsulation in microcapsules, if necessary, without any problems.
[0078] When the resin-reinforced glass ionomer cement composition for dental bonding of the present invention contains a photopolymerization initiator, the photopolymerization initiator is preferably contained in an amount of 0.01% by mass to 20% by mass, more preferably 0.1% by mass to 15% by mass, based on the total amount of (e) polymerizable monomer. The resin-reinforced glass ionomer cement composition for dental bonding of the present invention may not contain a photopolymerization initiator. The resin-reinforced glass ionomer cement composition for dental bonding of the present invention may not contain a polymerization initiator other than the (a) aryl borate compound.
[0079] Furthermore, the resin-reinforced glass ionomer cement composition for dental bonding of the present invention may optionally contain a non-acid-reactive powder for the purpose of adjusting the handling properties, mechanical properties, or hardening properties, so long as the various properties are not adversely affected.
[0080] The non-acid-reactive powder that can be used in the dental resin-reinforced glass ionomer cement composition of the present invention can be used without any particular limitation as long as it does not contain an element that reacts with the acidic group of the (c) polyalkenoic acid. Examples of the non-acid-reactive powder include known dental fillers, such as inorganic fillers, organic fillers, and organic-inorganic composite fillers, which can be used alone or in combination. Among them, it is particularly preferable to use inorganic fillers. In addition, the shape of these non-acid-reactive powders is not particularly limited, and they may be any shape such as spherical, needle-like, plate-like, crushed, and scaly, and there is no problem even if they are aggregates. There is also no particular limitation on the average particle size of these non-acid-reactive powders, but it is preferable that it is 0.001 μm or more and 30 μm or less.
[0081] Specific examples of inorganic fillers include, but are not limited to, quartz, amorphous silica, ultrafine silica particles, various glasses that do not contain elements that react with acidic groups (including glasses produced by the fusion method, synthetic glasses by the sol-gel method, glasses produced by gas phase reactions, etc.), silicon nitride, silicon carbide, boron carbide, etc.
[0082] When the resin-reinforced glass ionomer cement composition for dental bonding of the present invention contains a non-acid-reactive powder, the non-acid-reactive powder is preferably contained in an amount of 0.001% by mass or more and 20% by mass or less based on the total composition. The resin-reinforced glass ionomer cement composition for dental bonding of the present invention may not contain a non-acid-reactive powder.
[0083] Furthermore, when the resin-reinforced glass ionomer cement composition for dental bonding of the present invention is in a paste form, a thickener can be optionally contained for the purpose of adjusting the paste properties within a range that does not adversely affect various characteristics.
[0084] The thickener that can be used in the resin-reinforced glass ionomer cement composition for dental luting of the present invention may be either an inorganic thickener or an organic thickener. Examples of the inorganic thickener include fumed silica, calcium carbonate, calcium silicate, magnesium silicate, and clay minerals such as saponite, montmorillonite, beidellite, vermiculite, sauconite, stevensite, hectorite, smectite, tietite, and sepiolite.
[0085] Examples of organic thickeners include methylcellulose, hydroxyethylcellulose, hydroxymethylcellulose, hydroxypropylcellulose, carboxymethylcellulose, sodium carboxymethylcellulose, calcium carboxymethylcellulose, carboxypolymethylene, sodium alginate, propylene glycol alginate, sodium polyacrylate, starch, sodium starch glycolate, starch phosphate, polyvinylpyrrolidone, carboxyvinyl polymer, khaya gum, gum arabic, karaya gum, guar gum, etc. These can be used alone or in combination of two or more.
[0086] When the resin-reinforced glass ionomer cement composition for dental bonding of the present invention contains a thickener, the thickener is preferably contained in the paste in an amount of 0.001% by mass to 10% by mass. The resin-reinforced glass ionomer cement composition for dental bonding of the present invention may not contain a thickener.
[0087] The resin-reinforced glass ionomer cement composition for dental luting of the present invention may contain any of a surfactant, a preservative, an antibacterial agent, a coloring agent, a fluorescent agent, an inorganic fiber material, an organic fiber material, and other conventionally known additives, as necessary. The resin-reinforced glass ionomer cement composition for dental luting of the present invention comprises a first agent containing (a) an aryl borate compound and (b) an acid-reactive glass powder, and a second agent containing (c) a polyalkenoic acid and (d) water, and at least one of the first agent and the second agent may contain only (e) a polymerizable monomer and one or more of the components specifically described in this specification. The resin-reinforced glass ionomer cement composition for dental luting of the present invention may contain only (a) an aryl borate compound, (b) a powder material containing an acid-reactive glass powder, (c) a polyalkenoic acid, (d) water, (e) a polymerizable monomer, and (f) an acidic component having a molecular weight of 500 or less. The resin-reinforced glass ionomer cement composition for dental bonding of the present invention can contain only one or more of (a) an aryl borate compound, (b) a powder material including an acid-reactive glass powder, (c) a polyalkenoic acid, (d) water, (e) a polymerizable monomer, and (f) an acidic component having a molecular weight of 500 or less, as well as the components specifically described herein.
[0088] The resin-reinforced glass ionomer cement composition for dental bonding of the present invention may be provided in any form, such as powder / liquid, paste / liquid, or paste / paste, so long as (a) an aryl borate compound and / or (b) an acid-reactive glass powder do not coexist with (c) a polyalkenoic acid and / or (f) an acidic component having a molecular weight of 500 or less in the presence of (d) water.
[0089] The form of the powder / liquid material may be a combination of a powder material containing (a) an aryl borate compound and (b) an acid-reactive glass powder with a liquid material containing (c) a polyalkenoic acid, (d) water, (e) a polymerizable monomer, and (f) an acidic component having a molecular weight of 500 or less; a combination of a powder material containing (a) an aryl borate compound, (b) an acid-reactive glass powder, and (f) an acidic component having a molecular weight of 500 or less with a liquid material containing (c) a polyalkenoic acid, (d) water, and (e) a polymerizable monomer; (a) a combination of a powder material containing (a) an aryl borate compound, (b) an acid-reactive glass powder, and (c) a polyalkenoic acid, and (f) an acidic component having a molecular weight of 500 or less with a liquid material containing (c) a polyalkenoic acid, (d) water, and (e) a polymerizable monomer; and (b) a combination of a powder material containing (a) an aryl borate compound, (b) an acid-reactive glass powder, and (c) a polyalkenoic acid, and (c) a liquid material containing (c) a polyalkenoic acid, (d) water, (e) a polymerizable monomer, and (f) an acidic component having a molecular weight of 500 or less.
[0090] The form of the paste / liquid material may be a combination of a paste containing (a) an aryl borate compound, (b) an acid-reactive glass powder, and (e) a polymerizable monomer with a liquid material containing (c) a polyalkenoic acid, (d) water, and (f) an acidic component having a molecular weight of 500 or less; a combination of a paste containing (a) an aryl borate compound, (b) an acid-reactive glass powder, and (e) a polymerizable monomer with a liquid material containing (c) a polyalkenoic acid, (d) water, (e) a polymerizable monomer, and (f) an acidic component having a molecular weight of 500 or less; a combination of a paste containing (a) an aryl borate compound, (b) an acid-reactive glass powder, and (d) water with a liquid material containing (c) a polyalkenoic acid, (d) water, (e) a polymerizable monomer, and (f) an acidic component having a molecular weight of 500 or less; Examples of the combination include, but are not limited to, a combination of (e) a polymerizable monomer and a liquid material containing an acidic component having a molecular weight of 500 or less (f); a combination of a paste containing (a) an aryl borate compound, (b) an acid-reactive glass powder, (d) water, and (e) a polymerizable monomer with a liquid material containing (c) a polyalkenoic acid, (d) water, and (f) an acidic component having a molecular weight of 500 or less; a combination of a paste containing (a) an aryl borate compound, (b) an acid-reactive glass powder, (d) water, and (e) a polymerizable monomer with a liquid material containing (c) a polyalkenoic acid, (d) water, (e) a polymerizable monomer, and (f) an acidic component having a molecular weight of 500 or less.
[0091] Examples of the paste / paste form include a combination of a first paste containing (a) an aryl borate compound, (b) an acid-reactive glass powder, and (e) a polymerizable monomer with a second paste containing (c) a polyalkenoic acid, (d) water, and (f) an acidic component having a molecular weight of 500 or less; a combination of a first paste containing (a) an aryl borate compound, (b) an acid-reactive glass powder, and (e) a polymerizable monomer with a second paste containing (c) a polyalkenoic acid, (d) water, (e) a polymerizable monomer, and (f) an acidic component having a molecular weight of 500 or less; a combination of a first paste containing (a) an aryl borate compound, (b) an acid-reactive glass powder, and (d) water with a second paste containing (c) a polyalkenoic acid, (d) water, (e) a polymerizable monomer, and (f) an acidic component having a molecular weight of 500 or less; Examples of the combination include, but are not limited to, a combination of a first paste containing (a) an aryl borate compound, (b) an acid-reactive glass powder, (d) water, and (e) a polymerizable monomer with a second paste containing (c) a polyalkenoic acid, (d) water, and (f) an acidic component having a molecular weight of 500 or less, and a combination of a first paste containing (a) an aryl borate compound, (b) an acid-reactive glass powder, (d) water, and (e) a polymerizable monomer with a second paste containing (c) a polyalkenoic acid, (d) water, (e) a polymerizable monomer, and (f) an acidic component having a molecular weight of 500 or less. EXAMPLES
[0092] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. The components (a) to (f) and other components used to prepare the dental resin-reinforced glass ionomer cement compositions of the examples and comparative examples, as well as their abbreviations, are as follows:
[0093] [(a) Aryl borate compound] <Aryl borate compound with four aryl groups in one molecule> TPBNa: Sodium tetraphenylborate TPBK: Potassium tetraphenylborate <Aryl borate compound having three aryl groups in one molecule> BTPB: 1,2-dicyclohexyl 4,4,5,5-tetramethylbiguanidinium = n-butyltriphenylborate
[0094] [(b) Acid-reactive glass powder] CK-Si-1: Silane-treated fluoroaluminosilicate glass powder 1 (50% particle size: 0.7 μm) CK-Si-2: Silane-treated fluoroaluminosilicate glass powder 2 (50% particle size: 2.3 μm)
[0095] [(c) Polyalkenoic acid] <Polyalkenoic acid having a carboxy group> PCA1: Acrylic acid homopolymer powder (weight average molecular weight: 30,000) PCA2: Acrylic acid-3-butene-1,2,3-tricarboxylic acid copolymer powder (weight average molecular weight: 80,000) PCA3: Acrylic acid homopolymer powder (weight average molecular weight: 1,000) PCA4: Acrylic acid homopolymer powder (weight average molecular weight: 350,000) <Polyalkenoic acid not having a carboxy group> PVSA: Polyvinyl sulfonic acid powder (weight average molecular weight: 10,000)
[0096] [(d)Water] Distilled water
[0097] [(e) Polymerizable monomer] Bis-GMA: 2,2-bis[4-[3-methacryloyloxy-2-hydroxypropoxy]phenyl]propane ·UDMA: Urethane dimethacrylate 3G: Triethylene glycol dimethacrylate HEMA: 2-hydroxyethyl methacrylate ·GDMA: Glycerol 1,3-dimethacrylate ·FOM-03006:N-[tris(3-acrylamidopropoxymethyl)methyl]acrylamide
[0098] [(f) Acidic components with molecular weight of 500 or less] <Acidic component having two or more carboxy groups and no polymerizable group> ·Tartaric acid Citric acid Malic Acid <Acidic component having one carboxy group and no polymerizable group> Propionic acid <Acidic component having two or more carboxy groups and a polymerizable group> 4-AET: 4-Acryloyloxyethyl trimellitate <Acidic component having no carboxy group but a polymerizable group> 10-MDP: 10-methacryloyloxydecyl dihydrogen phosphate
[0099] [others] ·BPO: Benzoyl peroxide ·KPS: Potassium peroxodisulfate DMBE: Ethyl p-dimethylaminobenzoate ·AA: Ascorbic acid p-TSNa: Sodium p-toluenesulfinate Aerosil R711: Fumed silica (average primary particle size: approx. 12 nm) Aerosil R8200: Fumed silica (average primary particle size: approx. 12 nm) Aerosil #200: Fumed silica (average primary particle size: approx. 12 nm)
[0100] The methods for producing the silane-treated fluoroaluminosilicate glass powders 1 and 2 are as follows.
[0101] [Preparation of fluoroaluminosilicate glass powder 1] After mixing various raw materials such as silicon dioxide, aluminum oxide, aluminum phosphate, sodium fluoride, and strontium carbonate (glass composition: SiO2 26.4 wt%, Al2O3 29.3 wt%, SrO 20.5 wt%, PO5 10.9 wt%, Na2O 2.5 wt%, F 10.4 wt%), the raw material mixture was melted in a melting furnace at 1600°C. The molten liquid was removed from the melting furnace and quenched in water to obtain glass. The obtained glass was pulverized until the 50% particle size was 0.7 μm, and fluoroaluminosilicate glass powder 1 was obtained. The 50% particle size was measured using a laser diffraction particle size measuring device (Microtrac MT3300EXII: manufactured by Nikkiso Co., Ltd.).
[0102] [Preparation of fluoroaluminosilicate glass powder 2] After mixing various raw materials such as silicon dioxide, aluminum oxide, aluminum phosphate, sodium fluoride, and strontium carbonate (glass composition: SiO2 27.0 wt%, Al2O3 32.5 wt%, SrO 12.8 wt%, P2O5 10.4 wt%, Na2O 4.5 wt%, F 12.8 wt%), the raw material mixture was melted in a melting furnace at 1600°C. The molten liquid was removed from the melting furnace and quenched in water to obtain glass. The obtained glass was pulverized until the 50% particle size was 2.3 μm, and fluoroaluminosilicate glass powder 2 was obtained. The 50% particle size was measured using a laser diffraction particle size measuring device (Microtrac MT3300EXII: manufactured by Nikkiso Co., Ltd.).
[0103] [Silane treatment of fluoroaluminosilicate glass powders 1 and 2] 200g of fluoroaluminosilicate glass powder 1 or 2 was dispersed in 500ml of water, and then 2g of 3-methacryloyloxypropyltrimethoxysilane was added and stirred at room temperature for 2 hours. After removing the solvent, the mixture was further dried at 100°C for 5 hours to obtain silane-treated fluoroaluminosilicate glass powder 1 and 2 (CK-Si-1 and 2).
[0104] [Preparation of paste material] The components were mixed in the ratios shown in Tables 1 to 3 to prepare the first part (paste) and the second part (paste) of the resin-reinforced glass ionomer cement compositions for dental luting of the Examples and Comparative Examples.
[0105] [Preparation of powder and liquid materials] The components were mixed in the ratios shown in Tables 4 to 6 to prepare the first part (powder material) and the second part (liquid material) of the resin-reinforced glass ionomer cement compositions for dental luting of the Examples and Comparative Examples.
[0106] Composition (mass%) of the first agent (paste) used in the examples and comparative examples [Table 1]
[0107] Composition (mass%) of the second agent (paste) used in the examples and comparative examples [Table 2]
[0108] Composition (mass%) of the second agent (paste) used in the examples and comparative examples [Table 3]
[0109] Composition (mass%) of the first agent (powder material) used in the examples and comparative examples [Table 4]
[0110] Composition (mass%) of the second agent (liquid material) used in the examples and comparative examples [Table 5]
[0111] Composition (mass%) of the second agent (liquid material) used in the examples and comparative examples [Table 6]
[0112] The dental resin-reinforced glass ionomer cement compositions for luting (Examples 1 to 66, Comparative Examples 1 to 30) were prepared by mixing the first and second parts in the combinations and mass ratios shown in Tables 7 to 10, and the removability of excess cement and the tensile bond strength were evaluated. The evaluation methods are shown below.
[0113] [Evaluation of excess cement removal] The first and second parts corresponding to the resin-reinforced glass ionomer cement compositions for dental luting of the Examples or Comparative Examples were mixed in the ratios shown in Tables 7 to 10 for 20 seconds in the paste / paste form or for 30 seconds in the powder / liquid form, and then 0.3 g of the mixture was applied to the center of the upper surface of a resin block (12 mm long x 16 mm wide x 10 mm high). A resin block of the same shape was pressed firmly vertically against the mixed mixture-applied surface so that the sides of the same length overlapped, causing the mixed mixture to protrude from between the resin blocks. After that, the mixture was left at rest at 23 ° C., and 2, 3, and 4 minutes after the start of mixing, the kneaded material that protruded from between the resin blocks was removed as excess cement using an instrument (thin) (MiCD instrument # 2 (tip diameter φ 0.3 mm, manufactured by Matsufu)) or an instrument (thick) (MiCD instrument # 4 (tip diameter φ 1.5 mm, manufactured by Matsufu)), and the removability of the excess cement was evaluated according to the following evaluation criteria. In addition, if the evaluation result was A or B, it was determined that the state was semi-hardened and suitable for removing excess cement. In addition, if the evaluation results 2 minutes, 3 minutes, and 4 minutes after the start of mixing were A or B consecutively (if the evaluation results after 2 minutes and 3 minutes, 3 minutes and 4 minutes, or after 2 minutes, 3 minutes and 4 minutes were a combination of A and A, a combination of A and B, a combination of B and A, or a combination of B and B), it was determined that the excess cement had good removability. In the case of such a combination of consecutive evaluations, A was assigned 2 points and B was assigned 1 point, and it was determined that the higher the total score, the better the removability of excess cement. [Evaluation Criteria] A: The excess cement is in a semi-hardened state and can be easily removed in one piece using a thin instrument (MiCD instrument #2, tip diameter φ0.3 mm). B: The excess cement is in a semi-hardened state. When a thin instrument (MiCD instrument #2, tip diameter φ0.3 mm) is used, the excess cement breaks off and cannot be removed in one piece. However, when a thick instrument (MiCD instrument #4, tip diameter φ1.5 mm) is used, the excess cement can be easily removed in one piece. C: Although the excess cement is semi-hardened, it is easily torn off and cannot be easily removed in one piece even using a thick instrument (MiCD instrument #4, tip diameter φ1.5 mm), but it is possible to remove the excess cement. D: The excess cement has hardened and is difficult to remove even using a thick instrument (MiCD instrument #4, tip diameter φ1.5 mm). E: The excess cement is unhardened and difficult to remove even with a thick instrument (MiCD instrument #4, tip diameter φ1.5 mm).
[0114] [Tensile adhesion strength test] A test piece in which a bovine anterior tooth was embedded in epoxy resin was polished with waterproof abrasive paper #600 to expose the enamel plane. On the other hand, the surface of a cylindrical stainless steel rod (φ4.5 mm) was sandblasted (0.2 MPa) with alumina particles (average particle size 50 μm), and then washed with water and dried. The first and second agents corresponding to the resin-reinforced glass ionomer cement compositions for dental luting of the Examples and Comparative Examples were mixed in the proportions shown in Tables 7 to 10 for 20 seconds in the paste / paste form and for 30 seconds in the powder / liquid form, and then an appropriate amount of the mixture was applied to the surface of the stainless steel rod and pressed against the polished enamel plane. The excess cement was removed while a load of 10 N was applied to the upper surface of the stainless steel rod, and the mixture was cured for 5 minutes in an environment of 37°C and humidity of 90% or more. After curing, the 10 N load was removed, and the specimen was left to stand for 1 hour in an environment of 37°C and humidity of 90% or more, and then immersed in water at 37°C for 24 hours to prepare an adhesion test specimen. The tensile bond strength of the prepared adhesion test specimen was measured at a crosshead speed of 0.75 mm / sec using a universal testing machine (manufactured by Instron Corporation). [Evaluation Criteria] It was determined that the adhesive strength was 6 MPa or more, which is excellent and sufficient for use. It was determined that a usable adhesive strength was between 4 MPa and less than 6 MPa. If the adhesive strength was less than 4 MPa, it was determined that the adhesive strength was not suitable for use.
[0115] Evaluation results [Table 7]
[0116] Evaluation results [Table 8]
[0117] Evaluation results [Table 9]
[0118] Evaluation results [Table 10]
[0119] <Examples 1 to 66> Examples 1 to 66 had good removability of excess cement. Furthermore, they also showed excellent adhesion to tooth structure sufficient for use, and had desirable properties as a resin-reinforced glass ionomer cement for dental luting.
[0120] <Comparative Examples 1 to 3> The second agents used in Comparative Examples 1 to 3 had a high ratio of polyalkenoic acid (c) in the ratio of polyalkenoic acid (c) to water (d) contained in the second agent. The evaluation of Comparative Example 1 revealed that it had low adhesion to tooth structure. The evaluation of Comparative Examples 2 and 3 revealed that it was difficult to remove excess cement and had low adhesion to tooth structure. <Comparative Examples 4 to 6> The second agents used in Comparative Examples 4 to 6 have a high content of (c) polyalkenoic acid. In addition, the ratio of (c) polyalkenoic acid to (d) water contained in the second agents is also high. As a result of evaluating Comparative Examples 4 to 6, it was found that the removability of excess cement was poor and the adhesion to tooth structure was also low. <Comparative Examples 7 to 9> The second agents used in Comparative Examples 7 to 9 have a low content of (c) polyalkenoic acid. In addition, the ratio of (c) polyalkenoic acid to (d) water contained in the second agents is also low. As a result of evaluating Comparative Examples 7 to 9, it was found that the removability of excess cement was poor and the adhesion to tooth structure was also low. <Comparative Examples 10 to 12> The second agents used in Comparative Examples 10 to 12 have a low content of polyalkenoic acid (c). In addition, the ratio of polyalkenoic acid (c) to water (d) contained in the second agent is also low. On the other hand, the first agents used in Comparative Examples 10 to 12 contain polyalkenoic acid (c), which compensates for the shortage of polyalkenoic acid (c) in the second agent. However, evaluation of Comparative Examples 10 to 12 revealed poor removability of excess cement and low adhesion to tooth structure. <Comparative Examples 13 and 14> The second agents used in Comparative Examples 13 and 14 had a high content of (c) polyalkenoic acid. As a result of evaluating Comparative Examples 13 and 14, it was found that the removability of excess cement was poor and the adhesion to tooth structure was also low. <Comparative Examples 15 and 16> The second agents used in Comparative Examples 15 and 16 had a low content of (c) polyalkenoic acid. As a result of evaluating Comparative Examples 15 and 16, it was found that the removability of excess cement was poor and the adhesion to tooth structure was also low. <Comparative Examples 17 and 18> The second agents used in Comparative Examples 17 and 18 had a small ratio of (c) polyalkenoic acid in the ratio of (c) polyalkenoic acid to (d) water contained in the second agent. As a result of evaluating Comparative Examples 17 and 18, it was found that the removability of excess cement was poor and the adhesion to tooth structure was also low. <Comparative Example 19> Comparative Example 19 does not contain an (a) aryl borate compound, but contains AA and DMBE as other chemical polymerization initiators. As a result of evaluating Comparative Example 19, it was found that the removability of excess cement was poor and the adhesion to tooth structure was also low. <Comparative Example 20> Comparative Example 20 does not contain the (a) aryl borate compound, but contains BPO, AA, and DMBE as other chemical polymerization initiators. As a result of evaluating Comparative Example 20, it was found that the removability of excess cement was poor. <Comparative Example 21> Comparative Example 21 does not contain an (a) aryl borate compound, but contains p-TSNa as another chemical polymerization initiator. As a result of evaluating Comparative Example 21, it was found that the removability of excess cement was poor and the adhesion to tooth structure was also low. <Comparative Example 22> The second agent used in Comparative Example 22 had a high ratio of polyalkenoic acid (c) in the ratio of polyalkenoic acid (c) to water (d) contained in the second agent. As a result of evaluating Comparative Example 22, it was found that the adhesiveness to tooth structure was also low. <Comparative Example 23> The second agent used in Comparative Example 23 has a high content of (c) polyalkenoic acid. In addition, the ratio of (c) polyalkenoic acid to (d) water contained in the second agent is also high. As a result of evaluating Comparative Example 23, it was found that the removability of excess cement was poor and the adhesion to tooth structure was also low. <Comparative Example 24> The second agent used in Comparative Example 24 has a low content of (c) polyalkenoic acid. In addition, the ratio of (c) polyalkenoic acid to (d) water contained in the second agent is also low. As a result of evaluating Comparative Example 24, it was found that the removability of excess cement was poor and the adhesion to tooth structure was also low. <Comparative Example 25> The second agent used in Comparative Example 25 has a low content of (c) polyalkenoic acid. The ratio of (c) polyalkenoic acid to (d) water contained in the second agent is also low. On the other hand, the first agent used in Comparative Example 25 contains (c) polyalkenoic acid, which compensates for the shortage of (c) polyalkenoic acid in the second agent. However, the evaluation of Comparative Example 25 revealed that the removability of excess cement was poor and the adhesion to tooth structure was also low. <Comparative Example 26> The second agent used in Comparative Example 26 had a high content of (c) polyalkenoic acid. As a result of evaluating Comparative Example 26, it was found that the removability of excess cement was poor and the adhesion to tooth structure was also low. <Comparative Example 27> The second agent used in Comparative Example 27 had a low content of (c) polyalkenoic acid. As a result of evaluating Comparative Example 27, it was found that the removability of excess cement was poor and the adhesion to tooth structure was also low. <Comparative Example 28> The second agent used in Comparative Example 28 had a small ratio of (c) polyalkenoic acid in the ratio of (c) polyalkenoic acid to (d) water contained in the second agent. As a result of evaluating Comparative Example 28, it was found that the removability of excess cement was poor and the adhesion to tooth structure was also low. <Comparative Example 29> Comparative Example 29 does not contain the (a) aryl borate compound, but contains BPO (1 mass%), KPS, AA and p-TSNa as other chemical polymerization initiators. As a result of evaluating Comparative Example 29, it was found that the removability of excess cement was poor. <Comparative Example 30> Comparative Example 30 does not contain the (a) aryl borate compound, but contains BPO (0.01 mass%), KPS, AA and p-TSNa as other chemical polymerization initiators. As a result of evaluating Comparative Example 30, it was found that the removability of excess cement was poor. [Industrial Applicability]
[0121] The resin-reinforced glass ionomer cement composition for dental bonding of the present invention exhibits excellent adhesion to tooth structure, and can maintain a semi-hardened state suitable for removing excess cement for a long period during the hardening process, and the excess cement in the semi-hardened state has the property of being difficult to tear, making it useful as a dental cement.
Claims
1. The composition comprises a first part including (a) an aryl borate compound and (b) an acid-reactive glass powder, and a second part including (c) a polyalkenoic acid and (d) water; A resin-reinforced glass ionomer cement composition for dental bonding, comprising at least one of the first and second parts, (e) a polymerizable monomer, A resin-reinforced glass ionomer cement composition for dental bonding, characterized in that the content of the (c) polyalkenoic acid contained in the second agent relative to the entire second agent is in the range of more than 20% by mass and less than 70% by mass, and the content of the (c) polyalkenoic acid contained in the second agent in a total of 100 parts by mass of the (c) polyalkenoic acid contained in the second agent and the (d) water contained in the second agent is in the range of more than 45 parts by mass and less than 75 parts by mass.
2. 2. A resin-reinforced glass ionomer cement composition for dental bonding as described in claim 1, wherein the content of (c) polyalkenoic acid contained in the second agent relative to the entire second agent is in the range of more than 25% by mass and less than 65% by mass.
3. 3. A resin-reinforced glass ionomer cement composition for dental bonding according to claim 1, wherein the content of the polyalkenoic acid (c) contained in the second agent is in the range of more than 50 parts by mass and less than 75 parts by mass per 100 parts by mass of the polyalkenoic acid (c) contained in the second agent and the water (d) contained in the second agent.
4. 3. A resin-reinforced glass ionomer cement composition for dental bonding according to claim 1, wherein the content of the polyalkenoic acid (c) contained in the second agent is in the range of more than 52.5 parts by mass and less than 75 parts by mass per 100 parts by mass of the polyalkenoic acid (c) contained in the second agent and the water (d) contained in the second agent.
5. 2. The resin-reinforced glass ionomer cement composition for dental luting according to claim 1, wherein the acidic group of the polyalkenoic acid (c) is a carboxy group.
6. 2. The resin-reinforced glass ionomer cement composition for dental luting according to claim 1, further comprising: (f) an acidic component having a molecular weight of 500 or less.
7. 7. The dental resin-reinforced glass ionomer cement composition according to claim 6, wherein the acidic group possessed by the acidic component (f) having a molecular weight of 500 or less is a carboxy group.
8. 8. The resin-reinforced glass ionomer cement composition for dental luting according to claim 7, wherein the acidic component (f) having a molecular weight of 500 or less has two or more carboxy groups.
9. 9. The resin-reinforced glass ionomer cement composition for dental bonding according to claim 6, wherein the acidic component (f) having a molecular weight of 500 or less does not have a polymerizable group.
Citation Information
Patent Citations
Powder liquid-type dental resin-enriched glass ionomer cement
JP2014181190A